Arendt, Augustine And Evil - Grumett, David (Heythrop journal, 2000)
The publication of Hannah Arendt's doctoral these Love and Saint Augustine forces reappraisal of the view that Arendt's concept of evil originates in her experience of totalitarianism and coverage of the Eichmann trial. Augustine's account of the original nature of evil in the contexts of ontology, society and divine providence in fact provides the basis for Arendt's analysis of the banality of evil in the individual, the social, and the political spheres. Augustine's internal and external mental triads moreover contribute to Arendt's own thinking-willing-judging triad and allow a clearer understanding of its dynamics. The fact that Arendt's analysis derives much of its power from her appropriation of Augustinian theological concepts suggests a need for the increased diffusion of theological concepts in political thought.